THE EFECTIVENESS OF RHETORIC-BASED ESSAY WRITING TEACHING MODEL WITH CONTEXTUAL APPROACH - Akbar, Akbar; HP, Achmad (PPs UNJ, 2015)
This study aims to develop a rhetoricâbased essay writing teaching model with contextual approach in order to improve essay writing skills of students in the English Department of the Education and Teaching Faculty of Lakidende University of Konawe. This instructional model was developed by using research and development. The results show that the model can improve studentsâ essay writing skills effectively.. It was done in experimental class of the Education and Teaching Faculty of Lakidende University of Konawe Southeast Sulawesi province of Indonesia with the score of 69,80. Thus, it can be concluded that the rhetoricâbased essay writing teaching model with contextual approach that has been developed can improve the essay writing skills of students of English Department. It was proper.